Modern Approaches to Ensuring Learning Efficiency in the Educational Process - Boymurodova, G. T. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article focuses on the individual approach to the assessment of students, determining their intellectual development levels and making corrections in their activities, depending on the results of learning in the educational process. Also, parameters for monitoring and evaluating student knowledge are provided.